Terceirizar ou internalizar: um estudo avaliativo em uma IES pública - Dantas, Vilmar Secundina (2020)
This research deals with the phenomenon of outsourcing of labor services to the detriment of the internalization of labor services, in particular the services of Unarmed Patrimony and Cleaning and Conservation, passing through the observation of their general aspects and later particularizing for as implications related to the Public Service. In this sense, the general objective of this research was to analyze the relevant aspects for the effective decision making between the outsourcing and internalization of unarmed patrimonial surveillance services and cleaning and conservation of a Public University. The theoretical approach seeks to deal with the term outsourcing of public services, its concepts, definitions and historical evolution. It also addresses aspects related to public spending on outsourcing. As for the methodological aspects, this research is characterized, as for its purposes, as a descriptive study of exploratory character. It was decided to perform a triangulation between document analysis, observation and case study. Regarding the nature of the data, this is a cross-sectional survey of a qualitative and quantitative nature using primary data, collected through specific questionnaire and also using secondary data, obtained through documentary research at the institution under analysis with regard to expenses with outsourcing for the years 2014 to 2019. The questionnaires were applied to the managers of the researched University, characterized as a non-probabilistic sample, intentionally chosen, determined through the rate of return of the instrument applied in the data collection. The results indicate a good satisfaction with the outsourced services and that the transparency of service costs is essential in the decision-making process. Regarding costs, there was a relative ignorance of its composition by the respondents. In the case assessed, the comparative analysis of the costs of outsourcing versus internalization resulted in a higher overall cost for outsourced services in the period evaluated.